2021
DOI: 10.3389/fimmu.2021.620333
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Protein Tyrosine Phosphatase in Osteoimmunology

Abstract: Osteoimmunology highlights the two-way communication between bone and immune cells. T cell protein tyrosine phosphatase (TCPTP), also known as protein-tyrosine phosphatase non-receptor 2 (PTPN2), is an intracellular protein tyrosine phosphatase (PTP) essential in regulating immune responses and bone metabolism via dephosphorylating target proteins. Tcptp knockout in systemic or specific immune cells can seriously damage the immune function, resulting in bone metabolism disorders. This review provided fresh ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…When signals from immune and inflammatory responses stimulate cells, TC45 exits the nucleus and dephosphorylates receptor/nonreceptor‐type PTP kinases, such as Janus kinase (JAK), signal transducer and activator of transcription (STAT), 9 and epidermal growth factor receptor, to exert biological effects. Earlier reports have reported that PTPN2 limits the degree of tyrosine phosphorylation of JAKs by regulating the permeability of intestinal epithelial cells and dephosphorylates tyrosines on STAT1 and STAT3, thereby inhibiting cytokine expression mediated by cytokines such as INF‐γ and interleukin‐6 (IL‐6), modulating the signal transduction pathway of extracellular regulatory kinases, and inhibiting cell proliferation and differentiation 10,11 . PTPN2 expression is low in keratinocytes and is upregulated by 25‐hydroxyvitamin D3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When signals from immune and inflammatory responses stimulate cells, TC45 exits the nucleus and dephosphorylates receptor/nonreceptor‐type PTP kinases, such as Janus kinase (JAK), signal transducer and activator of transcription (STAT), 9 and epidermal growth factor receptor, to exert biological effects. Earlier reports have reported that PTPN2 limits the degree of tyrosine phosphorylation of JAKs by regulating the permeability of intestinal epithelial cells and dephosphorylates tyrosines on STAT1 and STAT3, thereby inhibiting cytokine expression mediated by cytokines such as INF‐γ and interleukin‐6 (IL‐6), modulating the signal transduction pathway of extracellular regulatory kinases, and inhibiting cell proliferation and differentiation 10,11 . PTPN2 expression is low in keratinocytes and is upregulated by 25‐hydroxyvitamin D3.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports have reported that PTPN2 limits the degree of tyrosine phosphorylation of JAKs by regulating the permeability of intestinal epithelial cells and dephosphorylates tyrosines on STAT1 and STAT3, thereby inhibiting cytokine expression mediated by cytokines such as INF-γ and interleukin-6 (IL-6), modulating the signal transduction pathway of extracellular regulatory kinases, and inhibiting cell proliferation and differentiation. 10,11 PTPN2 expression is low in keratinocytes and is upregulated by 25-hydroxyvitamin D3. Besides, PTPN2 also dephosphorylates protein substrates in the 8 JAK1/JAK3 signaling pathway and inhibits periodontal inflammation in type 2 diabetes.…”
mentioning
confidence: 99%
“…The inflammatory response initialed by hyperactivation of macrophages, such as the release of large amounts of cytokines and chemokines, is the dominant cause in the pathogenesis and continuous progression of UC [ 29 ]. T cell protein tyrosine phosphatase (TCPTP), also known as protein tyrosine phosphatase nonreceptor 2 (PTPN2), is an intracellular protein tyrosine phosphatase (PTP) that is widely expressed in various cells (such as, intestinal epithelial cells, macrophages, and T lymphocytes) and regulates immune responses by dephosphorylating target proteins [ 30 , 31 , 32 , 33 ]. Mutations of gene encoding TCPTP result in various autoimmune diseases such as IBD [ 34 ] and rheumatoid arthritis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of gene encoding TCPTP result in various autoimmune diseases such as IBD [ 34 ] and rheumatoid arthritis [ 35 ]. In vitro and in vivo experiments have proved that TCPTP can regulate multiple signaling pathways [ 36 , 37 , 38 , 39 ] by inhibiting Janus-activated kinases (JAK)/signal transducer and activator of transcription (STAT) [ 30 , 35 , 40 , 41 , 42 , 43 ]. The direct substrates include JAK3, STAT1, and STAT5 [ 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 T-cell protein tyrosine phosphatase (TC-PTP), encoded by PTPN2, is a non-receptor type PTP ubiquitously expressed in all tissues, with highest expression in hematopoietic cells. 3 TC-PTP negatively regulates signaling of non-receptor tyrosine kinases including JAK1 and JAK3, 4,5 receptor tyrosine kinases, 6,7 transcription factors, such as STAT1, 8 STAT3, 9 and STAT5, 5 and Src family kinases, including LCK. 10 Recently, accumulated evidence has suggested that TC-PTP is an attractive target for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%